Social Mobilization and Its Effectiveness in Mitigating the Adverse Effects of Climate Change on Vulnerability in the Niger Delta region - Okolie, Ugo Chuks; ETINAGBEDIA, Goodluck; EGBON, Thomastina Nkechi (International Journal of Public Administration and Policy, 2026)
This study examines the role of social mobilization in mitigating climate change impacts on vulnerable populations in the Niger Delta. This study adopted the cross-sectional survey design using questionnaire. Though the region constitutes nine states with a total population of 44,654,600, three States are purposely selected namely Bayelsa, Delta and Rivers with a population size of 15,650,300. A sample size of four hundred (400) was determined using the sample size Yemane’s formula. out of the four hundred (400) questionnaires distributed, only three hundred and seventeen (317) were retrieved from respondents, representing seventy-nine-point three percent (79.3%) response rate. The hypothesis was tested using linear regression and t-test at a 0.05 level of significance with the aid of the Statistical Package of Social Science (SPSS version 23.0). the study revealed that social mobilization significantly impacts the mitigation of climate change's adverse effects on vulnerable communities within Nigeria's Niger Delta. Regression analysis confirms that social mobilization plays a statistically significant role in reducing climate vulnerability. The concluded that a successful climate adaptation must be centered on the right policy tools that permeate all strategic ministries, departments and agencies at the state and regional institutions backed by strong political will, public awareness, stakeholders’ participation and consistent action plan which are not yet available and accessible in the Niger Delta region and therefore not being integrated in social development programmes. The study therefore recommended among others that governments at local and national levels should prioritize investments in the Niger Delta's infrastructure, healthcare, and educational facilities to build trust within communities. These improvements could foster a positive perception of governmental commitment and motivate community members to engage in climate resilience efforts.